Follow-up implementations on audit results in the local government of Banten Province - Sanjaya, Natta; Astuti, Retno Sunu; Wijayanto, Andi; Lituhayu, Dyah (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
Follow-up on implementing the recommendations based on the BPK audit result in the Banten Provincial Government has not been effective due to the completion time of the follow-up not being up to standard and the audited entity having difficulty carrying out the follow-up. This study aims to determine the effectiveness and challenges in implementing the policy of completing follow-up on the results of the BPK audit in the Banten Provincial Government. This study uses a descriptive qualitative approach and primary data collection techniques (observation and interviews) with informants purposively selected from BPK and local government. The technique used for data analysis is interactive models. Results show that the policy has not covered all target groups and has no impact on direct improvement changes. Decision-making has not supported the sustainability of completing follow-up audit results. The Inspectorate's mediation effectiveness is hindered by limited personnel and budget resources. Based on the implementation environment, actors have not been fully involved in monitoring the follow-up progress, and leaders do not have the commitment and assertiveness to encourage follow-up on audit results. The potential implication of this study suggests that the BPK should consider reformulating technical policies to ensure the effective and measurable completion of follow-up recommendations on audit results.